Managing endometriosis: a cross-sectional survey of women in Australia - Rebecca O’Hara; Heather Rowe; Jane Fisher (Journal of Psychosomatic Obstetrics and Gynecology, 2022)
Purpose Endometriosis is a chronic, inflammatory condition. The aim was to describe the self-reported disease characteristics and factors associated with the use of different treatment modalities among women with surgically diagnosed endometriosis. Method A cross-sectional online survey featuring 58 fixed-response items measuring disease characteristics, self-efficacy, health service usage, and treatment approaches was conducted. Logistic regression was used to explore the factors associated with different treatment modalities. Results Complete data were available from 620 respondents. Average delay to diagnosis was 6.4 years. Despite medical and surgical intervention, 65.8% reported dysmenorrhea and 61.1% reported dyspareunia, and 82.7% reported chronic pelvic pain in the last 3 months. Respondents had consulted an average of three different health practitioner specialties in the previous 12 months for their endometriosis. Discussion A chronic disease management plan (CDMP) may be a useful mechanism to coordinate multidisciplinary care among women who experience ongoing symptoms.